2017
DOI: 10.1016/j.ecoleng.2017.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Habitat suitability assessment of constructed wetlands for the smooth newt ( Lissotriton vulgaris [Linnaeus, 1758]): A comparison with natural wetlands

Abstract: Given the current decline of natural wetlands worldwide and the consequent negative impacts on amphibians, wetlands constructed for the treatment of wastewaters have the potential to play a role in the protection of these animals. However, there is a paucity of information regarding the value of constructed wetlands (CWs) to amphibians, particularly relating to the terrestrial phase of the life-cycle. This study compares the terrestrial habitats of natural wetlands (NWs) and CWs as refuges for the smooth newt … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 45 publications
0
16
0
Order By: Relevance
“…This often results in the creation of relatively simple and uniform habitat conditions for wildlife [112]. For example, a recent comparative assessment of habitat suitability in CWs and natural wetlands for the smooth newt (Lissotriton vulgaris) in Ireland found that natural wetlands had significantly more terrestrial habitat types than CWs [113].…”
Section: Cws Are Simplified Replications Of Natural Wetlandsmentioning
confidence: 99%
“…This often results in the creation of relatively simple and uniform habitat conditions for wildlife [112]. For example, a recent comparative assessment of habitat suitability in CWs and natural wetlands for the smooth newt (Lissotriton vulgaris) in Ireland found that natural wetlands had significantly more terrestrial habitat types than CWs [113].…”
Section: Cws Are Simplified Replications Of Natural Wetlandsmentioning
confidence: 99%
“…To date, most researches on wetlands restoration focused on restorability assessment [19,20,21,22], suitability prediction [23,24,25,26], restoration site selection [27,28,29,30,31], and so on. Qu et al (2018) proposed a GIS-based Restorability Index (RESI) model and restoration plan to evaluate the wetland restorability of the Sanjiang Plain, which is the largest marsh area of China [32].…”
Section: Introductionmentioning
confidence: 99%
“…Another difference between CWs and NWs refers to the hosting biodiversity, as NWs have considerably more habitat types than CWs [72]. Indeed, while NWs are commonly a habitat for native species, CWs often host non-native species and have the potential to increase the number of undesirable species [55].…”
Section: Natural and Constructed Wetlandsmentioning
confidence: 99%